Challenges of Tourism Marketing In Nepal: Global and Regional Perspective - Basnet, Bagala (Tribhuvan University Journal, 2010)
Tourism is very popular due to its growing importance in every sphere of human life. It is considered as a smokeless industry and has grown up very fasten the last few decades. It is a service industry and most sectors of it are labor-intensive and require relatively short training for most of the jobs. It is supported by hotels, airlines, travel and tour and handicrafts industries. The study of marketing helps to fulfill the needs and wants of the consumer or users in a better way. It also helps the service providers to earn sufficient profit through customer satisfaction. In the past, product oriented marketing has helped to increase visitor’s arrival. But in recent years, attention has been shifted from product destination to potential destination visitors. Nepal is a land of natural wonderland cultural mosaic. This small country in South Asia has unlimited possibilities of promoting various kinds of tourism. The only thing lacking is a will and enthusiasm on our part. Looking at the global trend, the competition towards getting the highest share of ever growing tourism industry, it is becoming fiercer and challenging. Now the time has come to improve the socio-economic condition of Nepal through the sustainable development of tourism and categorizing Nepal as one of the best destinations in the world.